Strategic Management of Organization Development and Civil Service Based PumpingHR Model at Ibn Khaldun University Bogor - Amir Tengku Ramly; Dudung Abdul Syukur (Integrated Journal of Business and Economics (IJBE), 2018)
Ibn Khaldun University which is the oldest Islamic campus in the city of Bogor founded by ulama leaders has a future interest to be a modern, leading-edge private campus with strong Islamic roots. This study aims to get UIKA's human resource management strategy that can become a strategic human resource for the achievement of UIKA's mission vision. This study is evaluative-descriptive, scientific literature search results with secondary data and modern theories of strategic management. UIKA's human resource development starts from creating a strategic plan, UIKA's future organizational structure and determining three important competency standards, namely (1) core competency standard, and (2) managerial competency standard, and (3) Supporting Competency.